2014
DOI: 10.1177/1076029614535973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing Plasma at –20°C for 2 Weeks on Prothrombin Time, Activated Partial Thromboplastin Time, Dilute Russell Viper Venom Time, Activated Protein C Resistance, and d-Dimer Levels

Abstract: To assess the impact of preanalytical variables of time and temperature on prothrombin time (PT), activated partial thromboplastin time (aPTT), dilute Russell viper venom time (DRVVT), activated protein C resistance (APCR), and d-dimer, samples from 23 healthy individuals and 18 patients having coagulopathy with known abnormal PT and aPTT were collected. Plasma from each individual was separately pooled and aliquoted; the first 2 aliquots were stored at room temperature then analyzed at 2 hours (baseline) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…For the analysis we chose a percentage change >10% from baseline results as clinically relevant difference between obtained results. The same percentage change was usually adopted by several authors, and according to our knowledge there are still no published guidelines of acceptable percentage changes for clinically relevant difference between results …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis we chose a percentage change >10% from baseline results as clinically relevant difference between obtained results. The same percentage change was usually adopted by several authors, and according to our knowledge there are still no published guidelines of acceptable percentage changes for clinically relevant difference between results …”
Section: Discussionmentioning
confidence: 99%
“…To assess the stability of samples, absolute, and percentage changes between results obtained at storage temperatures (RT and/or 4°C), and baseline results were calculated by using the following formula: [(result at storage temperature – baseline result)/baseline result] × 100. Clinically relevant difference was defined as a percentage change >10% …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen samples may also be used when longer storage periods (i.e. months or years) are needed, especially for research purposes [69][70][71][72].…”
Section: Stability Storage and Freeze-thaw Effectsmentioning
confidence: 99%
“…All studies published so far used multiple stability criteria except that performed by Betsou et al [70]. The review of D-dimer stability studies showed that a clinical cutoff of 10% was most frequently used [69,71,72,[75][76][77][78]. However, this 10% cutoff has not been derived from biological variation data.…”
Section: Stability Storage and Freeze-thaw Effectsmentioning
confidence: 99%